Legal Analysis of Article 3 Paragraph (1) and Article 2 Paragraph (1) of Law Number 20 of 2001 Concerning Amendments to Law Number 31 of 1999 on the Eradication of Corruption: A Study of Supreme Court Decision Number 1481 K/Pid.Sus/2018 - Sitepu, Syahnisura E Tuahta; Adawiyah, Rodiatun; Ginting, Deraldo Natalino (International Journal of Business, Law, and Education, 2025)
This resea.rch a.na.lyzes the a.pplica.tion of A.rticle 3 Pa.ra.gra.ph 1 a.nd A.rticle 2 Pa.ra.gra.ph 1 of La.w Number 20 Yea.r 2001 concerning the A.mendment to La.w Number 31 Yea.r 1999 concerning the Era.dica.tion of Corruption, pa.rticula.rly through a. ca.se study of the Supreme Court Decision Number 1481 K/Pid.Sus/2018. The study a.ims to delve into judicia.l considera.tions in deciding corruption ca.ses a.nd contribute to the development of concepts a.nd theories of justice in Indonesia.n crimina.l la.w. The method used is a. norma.tive juridica.l a.pproa.ch with descriptive- a.na.lytica.l methods. The findings of this resea.rch indica.te tha.t the Supreme Court's decision is in a.ccorda.nce with existing provisions, unlike the decisions of the District Court a.nd High Court which were not ba.sed on clea.r lega.l provisions, na.mely A.rticle 12 letter e combined with A.rticle 12 A. Pa.ra.gra.ph (2) of La.w Number 31 Yea.r 1999 Jo La.w Number 20 Yea.r 2001 concerning the Era.dica.tion of Corruption, which stipula.tes a. minimum imprisonment of 4 (four) yea.rs a.nd a. ma.ximum of 20 (twenty) yea.rs. This discrepa.ncy ha.s rendered the District Court a.nd High Court decisions inconsistent with a.pplica.ble la.w